Optimization of Solar Panel Power Estimation in Yogyakarta - Andi Ibrahim Soumi; Dona Setiawan; Fajar Fitriani; Abdul Hussamad; Andra Novriza Ramadan; V. Reza Bayu Kurniawan (Lembaga Publikasi Ilmiah dan Penerbitan (LPIP), 2025)
This research focuses on predicting the performance of photovoltaic (PV) systems using the PVWatts Calculator. The study examines three types of PV modules—Standard, Premium, and Thin Film—under the environmental conditions of Yogyakarta, Indonesia, with simulations set for the year 2024. Input parameters, including geographic coordinates, solar radiation intensity, average air temperature, and module specifications, were collected from reliable sources such as Suncalc. Simulations were conducted to evaluate annual and monthly energy outputs, considering factors such as system capacity, panel orientation, inverter efficiency, and system losses. The results show that Premium modules achieve the highest energy output, while Standard and Thin Film modules provide nearly comparable performance, making them cost-effective alternatives. Despite differences in efficiency, the performance gap between the module types remains relatively small under similar light intensity conditions. The findings highlight the importance of selecting PV modules based on specific needs, budget constraints, and environmental factors to optimize solar energy system performance. This study provides a comprehensive framework for PV performance calculations using PVWatts and offers valuable insights to support renewable energy development in the Yogyakarta region.